The miRNA landscape of leukemia – cellular actions to therapy through molecular mechanisms - Kang Zi Khor; Adam Azlan; Julia Joseph; Jeyrubini Ramesh; Maheswaran Solayappan; Yee Yik Mot; Mohamed Saleem; Narazah Mohd Yusoff; Emmanuel Jairaj Moses (Springer Nature, 2025)
The Nobel Prize in Physiology and Medicine awarded to Victor Ambros and Gary Rukum for their work in microRNA (miRNA) emphasized the important role that miRNA plays in biology. These conserved small noncoding RNA molecules play pivotal role especially in the post transcriptional stage of gene regulation, affecting various key cellular processes by interacting with target genes complement to the conserved miRNA seed sequence. Over the years miRNA was implicated in all manners of diseases with abnormal gene regulation especially in cancer. In leukemia, miRNA dysregulation could lead to aberrant cellular processes. These include but are not limited to leukemic development, survival and drug resistance. miRNA also have important clinical implications as differential miRNA abundance could contribute towards leukemogenesis. This is especially useful in the diagnosis and prognosis of leukemia. This review aims to explore and highlight the role of miRNAs in leukemia development, progression and to discuss miRNA involvement towards leukemic resistance to therapy.